The histone modification pattern of active genes revealed through genome-wide chromatin analysis of a higher eukaryote - Schübeler, Dirk (Cold Spring Harbor Laboratory Press, 2004)
The covalent modification of nucleosomal histones has emerged as a major determinant of chromatin structure and gene activity. To understand the interplay between various histone modifications, including acetylation and methylation, we performed a genome-wide chromatin structure analysis in a higher eukaryote. We found a binary pattern of histone modifications among euchromatic genes, with active genes being hyperacetylated for H3 and H4 and hypermethylated at Lys 4 and Lys 79 of H3, and inactive genes being hypomethylated and deacetylated at the same residues. Furthermore, the degree of modification correlates with the level of transcription, and modifications are largely restricted to transcribed regions, suggesting that their regulation is tightly linked to polymerase activity.